987. Repeated Exposure to an Adjuvanted Quadrivalent Subunit Influenza Virus Vaccine (aQIV): A Randomized, Observer Blind, Multicenter Study. (26th November 2018) - Daly, Wendy; Ramsey, Keith; Forsten, Aino; Heijnen, Esther; Leav, Brett; Oberye, Janine; Zhang, Bin; Pacciarini, Filippo; Vesikari, Timo
Abstract: Background: The safety, immunogenicity, and efficacy associated with administration of of aQIV in children 6 months through 5 years of age was investigated. 1 Although enhanced immunogenicity in children was demonstrated for MF59-adjuvanted influenza vaccines after first administration, the impact of repeated vaccination on immunogenicity and safety has not been evaluated. Methods: A total of 607 subjects who participated in parent study, now aged 12 months through 6 years, were enrolled the subsequent year and received a single dose of study vaccine. Enrolled subjects received the same type of influenza vaccine administered in the parent study (aQIV or nonadjuvanted comparator). Blood samples were taken for immunogenicity assessment prior to the second year vaccination, and 21 and 180 days after vaccination. Results: At baseline, approximately 12 months after vaccination in the parent study, subjects in the aQIV group had significantly greater geometric mean titer (GMT) values against all four homologous strains compared with subjects in the nonadjuvanted vaccine group. After year 2 vaccination, CBER criteria for seroconversion and hemagglutination inhibition (HI) titer ≥1:40 were met for the aQIV group for all four homologous strains tested at Day 22. At both Day 22 and Day 181, subjects who received aQIV had significantly greater GMT values for HI against all four homologous strains compared with those who received nonadjuvanted vaccine. Increased immune response of aQIV vs. nonadjuvanted vaccine was also observed for the selected heterologous strains tested at baseline, Day 22 and Day 181. In terms of safety, transient and generally mild to moderate reactogenicity was more commonly observed in the aQIV group vs. the nonadjuvanted group, but overall safety profiles were similar and comparable to the parent study. Conclusion: This first-year revaccination study in young children confirms enhanced immunogenicity and similar safety profile after repeat aQIV vaccination compared with repeat nonadjuvanted influenza vaccination. Reference 1.Vesikari T et al. Lancet Respir Med 2018;6:345–356. Disclosures: K. Ramsey, Seqirus: Investigator, Research support. Novartis: Investigator, Research support. E. Heijnen, Seqirus: Employee and Shareholder, Global Employee Share Plan and Salary. B. Leav, Seqirus: Employee and Shareholder, Salary. J. Oberye, Seqirus: Employee and Shareholder, Global Employee Share Plan and Salary. B. Zhang, Seqirus: Employee and Shareholder, Company stock and Salary. T. Vesikari, Seqirus: Consultant, Consulting fee.